The Influence of Tiktok as a Learning Media to Develop Youngsters' English Proficiency - Mooy, Adoni Seniputra; Marpaung, Tiarma; Hambandima, Erny Selfina Nggala (English Education Study Program - Artha Wacana Christian University, 2025)
TikTok's emergence as a global social media platform has demonstrated its potential as a powerful tool for developing English proficiency. Its engaging content, immersive experience, and interactive features provide learners with unique opportunities to enhance their language skills enjoyably and authentically. The influence of TikTok among youngsters has made it an appealing platform for them to be connected with English-learning videos from numerous English content creators. This research aims to answer two research questions: 1. What are the varieties of English learning types on TikTok that youngsters use use? 2. How does TikTok influence the development of English Proficiency among Youngsters? To answer those two questions, the writer applied the descriptive qualitative method, which was taken from 55 respondents who fall into the Gen Z category. After analyzing the data, the writer found that youngsters who learn English from TikTok experienced and saw the varieties of English learning types on TikTok: Short-form videos, language challenges, native speaker videos, and interactive learning. It has also been figured out how TikTok application as an English learning medium has shown its influence in developing youngsters' English proficiency, including the influence of TikTok towards youngsters' communication competence, creativity and critical thinking, self-directed learning, and English learning and teaching tool.